Влияние фрагментации ареала на генетическое разнообразие растений на примере двух редких видов флоры Украины Gentiana lutea L. и Iris pumila L. - Андреев, И.О.; Бублик, Е.Н.; Мосула, М.З.; Спиридонова, Е.В.; Дробык, Н.М.; Кунах, В.А. (Фактори експериментальної еволюції організмів, 2015)
Aims. The paper summarizes the results of population genetic studies of two rare species of the Ukrainian flora in order to identify factors that may affect the changes in the genetic diversity of populations caused by the reduction in the size and habitat fragmentation. Methods. Molecular genetic analysis using various types of dominant PCR markers, statistical methods for genetic data analysis. Results. It was found that, in perennials, genetic effects of habitat fragmentation and reduction in population size may remain indiscernible for some time. Reduced size in conditions of long-term isolation leads to a steady decline in intra-population variation and increasing divergence of the populations. Conclusion. When interpreting the results of the evaluation of the genetic diversity of rare plant species, it is important to consider lifehistory traits of the species and the history of populations. Keywords: genetic diversity, habitat fragmentation, rare species.